Suspension of Detention of Suspects in Framework of Realizing Human Rights Protection - Fitriani Akrima; Jawade Hafidz (Universitas Islam Sultan Agung, 2021)
The purpose of this research is 1) To find out and analyze the detention suspension process for suspects at the Bogor Police; 2) To find out and analyze about suspended detention to realize the protection of human rights, and to find out and analyze the obstacles in the implementation of suspension of detention and efforts to overcome them. The approach method used is Sociological juridical which in other words is a type of sociological legal research and can also be called field research, which examines the applicable legal provisions and what happens in reality in society. This research was analyzed using the theory of law enforcement, human rights and justice. The conclusion of this research is that the process of detention of a suspect at the Bogor Police is given to a suspect who has committed a criminal act and is carried out by the investigator, where the suspect in a criminal case filed strong and accountable reasons a request or request for a suspension of detention which can later be used as a basis for consideration and in accordance with Article 31 of the Criminal Procedure Code it has been stated that the suspension is carried out based on stipulated conditions, namely compulsory reporting, not leaving the house or not leaving the city.